2000
DOI: 10.1108/10610420010347128
|View full text |Cite
|
Sign up to set email alerts
|

Comparing bidding and pricing between in‐person and online auctions

Abstract: Examines the phenomenon of online auctions. Begins by developing a theoretical base for understanding how online and in-person auctions should differ in terms of consumer risk. Online auctions with seller reserve prices are compared to in-person auctions without seller reserve prices using data from 60 paired sales of collectible figurines. Online auctions are found to exceed in-person auctions in both mean initial bid prices and mean final sales prices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…Online auctions attract thousands, sometimes millions, of bidders for items ranging from commodities to collectibles (Massad and Tucker, 2000). Investors expect a tremendous amount of growth in online auctioning, assigning huge price/earning multiples to the major players in the industry (Massad and Tucker, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Online auctions attract thousands, sometimes millions, of bidders for items ranging from commodities to collectibles (Massad and Tucker, 2000). Investors expect a tremendous amount of growth in online auctioning, assigning huge price/earning multiples to the major players in the industry (Massad and Tucker, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effect of reserve pricing may be to lower the average price ultimately paid in seller reserve auctions, while increasing the average size of starting price [10] . Regarding auction interest, Vincent [11] argued that higher reserve prices have the effect of "increasing bidder participation at higher levels since the reserve would have the effect of eliminating low-valuation bidders from contention" [10] . Bajari and Hortacasu [12] found that the starting price is the most significant determinant of whether a bidder enters an auction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The economics literature has a long and rich history of research involving traditional auctions. In recent years, marketing researchers have used online auction data to study a number of phenomena in a wide array of product categories (e.g., Cheema et al 2012;Haruvy and Leszczyc 2010;Hou and Blodgett 2012;Jap 2003;Häubl and Leszczyc 2003;Kamins et al 2004;Li et al 2009;Massad and Tucker 2000;Leszczyc and Häubl 2010;Sinha and Greenleaf 2000;Weinberg and Davis 2005;Dholakia et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Kamins, et al (2004) used ANOVA and pairwise contrasts, and their data included no sale items. Massad and Tucker (2000) used bivariate regression and t tests, and only considered items that sold.…”
Section: Introductionmentioning
confidence: 99%